Expression and characterization of an intracellular cellobiose phosphorylase in Saccharomyces cerevisiae - Sadie, Christa J. (Christiena Johanna) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2007.